The relationship between emotional intelligence on students' productivity in selected Malaysia higher education institutions in the Post-Covid-19 pandemic - Md Noor, Nor Azian; Kareem, Poopla; Khalid, Nursyahidah (SEGi University, 2023)
Emotional intelligence in higher education institutions is crucial for administrations and students, especially post-Covid 19 pandemic. University students' emotions and feelings were down due to the sudden closure of campuses across the Globe. Emotional intelligence is an essential determinant of success and productivity in life. This study investigates the impact of emotional intelligence on students' productivity during remote teaching and learning. This study is conducted using aquantitative research approach. Data were collected from 180 respondents out of 200 questionnaires administered to university students in Malaysia during the post-Covid 19 pandemic. The results indicated that the student's emotional intelligence dimensions are significantly high. Summation Mean values range from (4.10) with standard deviation = 3.11 for selfregulation to (4.52) for social skills with SD (.621). The results further indicated a significant difference in students' emotional intelligence based on their nationalities and gender cohort. The study further showed the considerable impact of emotional intelligence on the students' productivity during remote teaching and learning in Malaysian higher education institutions. The results of the multiple regression analysis show that there is a relationship between the variables with (r= 0.003p=0.49). Therefore, the study recommends that the universities management and the educational administrations upgrade their technical and soft skills to enhance students' emotional intelligence